Cardiovascular risk factors, global cardiovascular risk, and vascular age in a cohort of Peruvian HIV patients - German Valenzuela-Rodriguez; Jaime A. Collins; Raul Castillo; Luis R. Illescas; Adrian V. Hernandez; Carlos Diaz-Arocutipa (HIV & AIDS Review. International Journal of HIV-Related Problems)
Introduction Data on cardiovascular risk and vascular age in patients with human immunodeficiency virus (HIV) from developing countries are scarce. Therefore, the current study aimed to determine the prevalence of cardiovascular risk factors, global cardiovascular risk, and vascular age in a Peruvian cohort of patients with HIV.